Pharmacists as important prescribers of coronavirus disease 2019 (COVID-19) antivirals. Issue 1 (11th July 2022) - Mahoney, Monica V.; Bhagat, Hita; Christian, Robbie; del Rio, Carlos; Hohmeier, Kenneth C.; Klepser, Michael E.; Pogue, Jason M.
Abstract: Although pharmacists are key members of the healthcare team, they are currently ineligible to independently prescribe the oral coronavirus disease 2019 (COVID-19) antivirals. We report the roles pharmacists have undertaken during the COVID-19 pandemic and provide evidence for the support of independent oral COVID-19 antiviral prescribing.